Earthquakes and active tectonics of the South Caspian region, Central Asia - Marshall, NR (2023)
The study of earthquakes and active faulting is vitally important at multiple scales. At a local level, analysis of past earthquakes and surface ruptures provides insight and source parameters that are critically important for effective seismic hazard assessment. More regionally, understanding characteristic earthquakes and active faulting helps reveal plate tectonic motion that influences deformation and sedimentation. Globally, as populations have expanded the number of people effected by earthquakes and active faulting has increased. By working in regions where environmental conditions allow earthquake and active fault signals to be well preserved, insight into fundamental earthquake rupture processes and complex rupture patterns can be gained. I investigate single complex events, such as the 1948 Ashgabat M 7.3 earthquake, using a combination of seismic and geomorphic data. I find that this is one of the most devastating earthquakes in the 20th Century occurring on a secondary active fault with a complicated rupture. From analysis of digitised seismograms, the earthquake had a strike-slip focal mechanism and had a hypocentroidal depth of 12 km. I examine geomorphic displacements and identify active faults in Ashgabat using high resolution satellite imagery. After reviewing historical records, imagery and rupture maps, I determine that the earthquake did not rupture the main tectonic fault (Main Kopeh Dagh Fault) in the region, but a secondary right-lateral strike-slip fault southeast of Ashgabat. Further west from Ashgabat, I look to use our understanding of active faulting to help constrain regional landscape evolution and paleoclimate signals. I investigate geomorphic displacements and stratigraphy along the Main Kopeh Dagh Fault and in the east Caspian lowlands. I build the first late-Quaternary stratigraphy in the Turkmen Kopeh Dagh and east Caspian lowlands, observing five different generations of alluvial fan deposits. I recalculate the geologic slip-rate on the Main Kopeh Dagh Fault to 9.2 ± 1.5 mm/yr and develop a new method that uses measurements of offset drainage channels and the geologic slip-rate to constrain the timing of alluvial fan incision. I find clusters of drainage channel displacements that I date, using the slip-rates, at 2 – 3 ka, 3 – 4 ka, 8 – 12 ka, 24 – 33 ka, 38 – 52 ka, 56 – 78 ka and 94 – 130 ka. I interpret these special and temporal clusters as periods on heightened incision, providing insights into the regional environment during the Holocene and late-Pleistocene.